Periodontite experimental como fator de risco na potencialização dos efeitos do imobilismo - Leite, Marcela Aparecida (2017)
Objective: To evaluate whether periodontal disease, through systemic inflammation, can potentiates the deleterious effects of immobilization of the skeletal striated muscle, contributing to the development of muscle atrophy due to disuse. Methods: Forty Wistar rats were divided into four groups: 1) Control Group (CG), 2) Periodontal Disease (GPD) 3) Immobilized (IG) and 4) Immobilized with Periodontal Disease (IPDG). Periodontal disease was induced for 30 days, with ligature method, and the immobilization of the right pelvic limb was performed with cast bandage for 15 days. Prior to euthanasia, the nociceptive threshold and muscular grasping force were evaluated. Afterwards, the soleus muscle was dissected and processed for sarcomere counting and morphological and morphometric analysis. For analysis of the data, the one-way ANOVA followed by the Tukey post test, with p < 0.05. Results: The IG and IPDG groups presented lower muscle weight, lower muscular grip strength and less number of sarcomeres compared to CG. The PDG showed reduction of muscle strength and nociceptive threshold after 15 days of periodontal disease and increase of connective tissue compared to CG. The IPDG presented lower muscle length and nociceptive threshold compared to the other groups. The IG presented a reduction in the cross-sectional area and a smaller diameter, an increase in the number of nuclei and a nucleus/fiber ratio, a decrease in the number of capillaries and a capillary/fiber ratio, with an increase in connective tissue. In the IPDG group, there were significant results for increased nucleus/fiber ratio, decreased capillaries and increased connective tissue when compared to the IG group. The IPDG group presented greater muscle tissue degeneration and increased inflammatory cells when compared to the other groups. Conclusion: Periodontal disease potentiated the deleterious effects of immobilization of the skeletal striated muscle, through intense destruction of muscle tissue, with significant increase of connective tissue, nucleus/fiber ratio and inflammatory infiltrate, significant reduction of vascularization and reduction of muscle length, with consequent reduction of muscle strength and nociceptive threshold.